Konstruksi Nilai Pendidikan Keimanan Islam dalam Prosa Fiksi Kecil-kecil Punya Karya - Muyassaroh Muyassaroh (Ta'allum: Jurnal Pendidikan Islam, 2017)
This research was conducted to describe (1) the value of Islamic educational background, (2) the literature product which used to develop Islamic educational background, and (3) the pattern of Islamic educational value in a fiction stories with the titled of Kecil-Kecil Punya Karya. This research was used qualitative design which applied hermeneutic text analysis procedure. The data was collected from verbal and non-verbal text which describe the habit, attitude, act and speech of the characters. Moreover, the data was collected through documentation technique. The results show that (1) the value of Islamic educational background is develop under 6 kinds of believe. They are first, the believe to God, then the believe to the Angel, the believe to the Holy book, the believe to Rasulullah, the believe to the judgement day, and the last is the believe to the destiny; (2)The literature pattern which shown in the prose that develop the Islamic educational background are consist of characters, setting and the moral value which covered in the story; (3) The pattern of Islamic educational values were divided under 4 stages. They are introduction, the value of understanding, habitual activities, and attitude. In conclusion, the researcher suggested to the parents to use those 4 stages since it is important to applied as the basic of live.